First synthesis of acylated nitrocyclopropanes - Iwai, Kento; Kamidate, Rikiya; Wada, Khimiya; Asahara, Haruyasu; Nishiwaki, Nagatoshi (Beilstein Journal of Organic Chemistry, 2023)
Although nitrocyclopropanedicarboxylic acid esters are widely used in organic syntheses, nitrocyclopropanes with an acyl group have not yet been synthesized. When adducts of β-nitrostyrene and 1,3-dicarbonyl compounds are treated with (diacetoxyiodo)benzene and tetrabutylammonium iodide, iodination occurs at the α-position of the nitro group, and the subsequent O-attack of the enol moiety leads to 2,3-dihydrofuran. Cyclopropane was successfully synthesized through C-attack as the acyl group became bulkier. The obtained nitrocyclopropane was transformed into furan upon treatment with tin(II) chloride via a ring-opening/ring-closure process.
Keywords: acetoxyiodine; conjugate addition; dihydrofuran; nitroalkene; nitrocyclopropane